Characterization of the biochemical properties of Campylobacter jejuni RNase III - Haddad, Nabila (Portland Press Ltd., 2013)
Campylobacter jejuni is a foodborne bacterial pathogen, which is now considered as a leading cause of human bacterial gastroenteritis. The information regarding ribonucleases in C. jejuni is very scarce but there are hints that they can be instrumental in virulence mechanisms. Namely, PNPase (polynucleotide phosphorylase) was shown to allow survival of C. jejuni in refrigerated conditions, to facilitate bacterial swimming, cell adhesion, colonization and invasion. In several microorganisms PNPase synthesis is auto-controlled in an RNase III (ribonuclease III)-dependent mechanism. Thereby, we have cloned, overexpressed, purified and characterized Cj-RNase III (C. jejuni RNase III). We have demonstrated that Cj-RNase III is able to complement an Escherichia coli rnc-deficient strain in 30S rRNA processing and PNPase regulation. Cj-RNase III was shown to be active in an unexpectedly large range of conditions, and Mn(2+) seems to be its preferred co-factor, contrarily to what was described for other RNase III orthologues. The results lead us to speculate that Cj-RNase III may have an important role under a Mn(2+)-rich environment. Mutational analysis strengthened the function of some residues in the catalytic mechanism of action of RNase III, which was shown to be conserved.